2013
DOI: 10.4172/2325-9590.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucellosis and Q-Fever in Southeast Ethiopian Pastoral Livestock

Abstract: To assess seroprevalences of and in pastoral livestock in southeast Ethiopia, a cross-sectional study was carried out in three livestock species (cattle, camels and goats). The study was conducted from July 2008 to August 2010, and eight pastoral associations (PAs) from the selected districts were included in the study. Sera from a total of 1830 animals, comprising 862 cattle, 458 camels and 510 goats were screened initially with Rose Bengal plate test (RBPT) for . All RBPT positive and 25% of randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
57
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 24 publications
23
57
9
Order By: Relevance
“…39 In support of this fact, a recent serological study reported antibodies against C. burnetii in 54.2% of goats, 31.6% of cattle, and 90% of camels in eastern parts of Ethiopia. 23 In our study, a statistically significantly higher (MH, P 0.0001) prevalence of positive C. burnetii DNA in ticks was observed in southeastern districts from the Borana zone (Arero, Moyale, and Yabelo) than in the central districts (Kimbibit and Arsi). This difference is most probably attributable to factors such as the presence of larger population of cattle, goats, sheep, and camel that are usually managed by a pastoral type of management characterized by unrestricted movement of animals in search of water and grazing pasture in districts in the Borana zone.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…39 In support of this fact, a recent serological study reported antibodies against C. burnetii in 54.2% of goats, 31.6% of cattle, and 90% of camels in eastern parts of Ethiopia. 23 In our study, a statistically significantly higher (MH, P 0.0001) prevalence of positive C. burnetii DNA in ticks was observed in southeastern districts from the Borana zone (Arero, Moyale, and Yabelo) than in the central districts (Kimbibit and Arsi). This difference is most probably attributable to factors such as the presence of larger population of cattle, goats, sheep, and camel that are usually managed by a pastoral type of management characterized by unrestricted movement of animals in search of water and grazing pasture in districts in the Borana zone.…”
Section: Discussionsupporting
confidence: 40%
“…Livestock comprising cattle, goats, sheep, and camels in Arero, Moyale, and Yabelo districts (Borana zone) are kept under a pastoral type of animal management. 23,27 This system is characterized by very large animal populations, and livestock are the main source of human food from milk and milk byproducts and the main source of income for farmers, whereas in all other study districts, animals, including cattle, sheep, goats, and equines, are kept under a crop-animal mixed type of management with extensive production systems. 23,27 Collection and identification of ticks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by Hussein and others [15] an even higher prevalence (62%) was observed in Saudi camels. Similarly, high prevalence (66%) were recorded in camels in Egypt [24], Chad (80%) [25] and also in nomadic camels (100%) in eastern Ethiopia [26]. This exceptionally high prevalence could be attributed to poor hygienic and management conditions under which camels are kept, as well as their heavy exposure to contaminated dust and sand during sandstorms in desert areas.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical distribution of the disease is limited. However, it is still a major problem in livestock industry in the Asia, Africa, Latin American, and the Mediterranean regions [5,6]. …”
Section: Introductionmentioning
confidence: 99%